MPS 01-01 A CONSERVED microRNA CLUSTER AS A POTENTIAL MASTER GENE EXPRESSION REGULATOR IN ANGIOTENSIN II-INDUCED VASCULAR DAMAGE. (September 2016) - Paradis, Pierre; Huo, Ku-Geng; Barhoumi, Tlili; Fraulob-Aquino, Júlio C.; Richer, Chantal; Lajoie, Mathieu; Sinnett, Daniel; Schiffrin, Ernesto L.
Abstract : Objective: Non-coding RNAs (ncRNAs), including long ncRNAs (lncRNAs) and microRNAs (miRNAs), account for ∼98% of the transcribed RNAs. They have been shown to play a role in cardiovascular disease. Vascular damage is an early manifestation and a cause of end-organ damage in hypertension. However, it is unknown whether ncRNAs are involved in the development of vascular injury in hypertension. We hypothesize that ncRNA regulation plays a role in vascular remodeling in hypertension. Design and Method: Ten week-old male C57BL/6 mice underwent sham surgery or angiotensin (Ang) II infusion for 7 or 14 days. Blood pressure (BP) was measured by telemetry. Total RNA was extracted from mesenteric arteries and used to construct libraries for total RNA and small RNA deep sequencing using Illumina HiSeq-2500. Differential expression analysis and heat maps were made in R. Targetscan was used to predict interactions between differentially expressed miRNAs (DEmiRs) and genes (DEGs). MEME Suite was used to predict differentially expressed transcription factor targets in the DEGs. Cytoscape was used to perform functional enrichment analysis and construct molecular networks integrating the above interactions and the gene expression profile. Results: Differentially expressed mRNAs, lncRNAs, miRNAs and other small ncRNAs were identified in the Ang II-treated groups. Functional enrichment analysis showed enrichment of extracellular matrix in both 7-day and 14-day Ang II-induced DEGs, but developmental process in only the 14-day Ang II-induced DEGs. We identified 10 DEmiRs whose expression levels were correlated with BP, 9 of which are located in a single miRNA cluster that is highly conserved in humans. Conclusions: We have identified a conserved miRNA cluster that may play a pivotal role in the regulation of vascular damage. A sub-network of genes presenting the interaction between the miRNA cluster and other BP-correlated ncRNAs has been selected for future investigation to identify therapeutic targets.